Orthogonal Nano‐Engineering (ONE): Modulating Nanotopography and Surface Chemistry of Aluminum Oxide for Superior Antibiofouling and Enhanced Chemical Stability - Hanyu Chen; Felicia Fianu; Carmen I. Moraru; Rong Yang; Yifan Cheng (Advanced Materials Interfaces)
Abstract Decoupling certain material surface properties can be key to attaining critical property‐activity relationships that underpin their antibiofouling performance. Here, orthogonal nano‐engineering (ONE) is employed to decouple the influences of nanotopography and surface chemistry on surface antibiofouling. Nanotopography and surface chemistry are systematically varied with a two‐step process. Controlled nanotopography is obtained by electrochemical anodization of aluminum, which generated anodic aluminum oxide (AAO) surfaces with cylindrical nanopores (diameters: 15, 25, and 100 nm). To modify surface chemistry while preserving nanotopography, an ultrathin (≈5 nm) yet stable zwitterionic coating of poly(divinylbenzene‐4‐vinylpyridyl sulfobetaine) is deposited on these surfaces using initiated chemical vapor deposition (iCVD). Antibiofouling performance is assessed by quantifying 48‐h biomass formed by gram positive and negative bacteria. The ONE surfaces demonstrated enhanced antibiofouling performance, with small‐pore nanotopography and zwitterionic chemistry each lowered biomass accumulation by tested species, with potential additive effects. The most effective chemistry‐topography combination (ZW‐AAO15) enabled an overall reduction of 91% for Escherichia coli, 76% for Staphylococcus epidermidis, 69% for Listeria monocytogenes, and 67% for Staphylococcus aureus, relative to the uncoated nanosmooth control. Additionally, the composite ZW coating exhibited encouraging anticorrosion properties under both static and turbulent cleaning conditions, vital to antibiofouling applications in healthcare and food industries.